Previously misdiagnosed linear IgA dermatosis resolved with dapsone. (25th April 2018) - Tieppo Francio, Vinicius; Towery, Chris; Davani, Saeid; Allen, Travis; Brown, Tony L
Abstract : This is the case of a 25-year-old African American woman with a 3-week history of itching with burning, blistering lesions on her torso and extremities. Medical history was unremarkable. Medical treatments included three visits to urgent care, where she was treated with antivirals, oral and topical steroids, antibiotics and antifungals unsuccessfully. We performed a skin biopsy, and immunoflorescent studies revealed a linear deposition of IgA antigen at the basement membrane. The clinical diagnosis of linear IgA dermatosis (LAD) was established, with no eliciting cause, other than potential occupational exposure to Chlamydophila psittaci via her employment in a pet store. This is the first case to our knowledge to report such an association. However, confirmation of the exposure would only establish correlation, not causality. Resolution of symptoms and blisters was achieved with dapsone treatment. Accordingly, we highlight the crucial importance of reviewing exposures, along with the potential aetiology of LAD.